Universal Provision, Indigeneity and the Treaty of Waitangi - Durie, Mason (Victoria University of Wellington Law Review, 2002)
This article provides an overview of Māori recognition in statutes and the political sphere, and affirms the Treaty of Waitangi’s status as a partnership between the indigenous Māori and the Crown rather than a document that puts Māori on the sidelines. The Treaty of Waitangi has a critical part to play in defining the relationship between the Māori and the Crown. It is therefore argued that the challenge is not whether indigeneity should be recognised at all, but rather how to recognise indigeneity while treating all citizens fairly. The author concludes that the Crown must recognise the Treaty relationship, indigeneity, and citizenship in statutes, policies, state programmes and other measures and indicators.